Fenton chemistry and oxidative stress mediate the toxicity of the beta-amyloid peptide in a Drosophila model of Alzheimer's disease. - Rival, T.; Page, R.M.; Chandraratna, D.S.; Sendall, T.J.; Ryder, E.; Liu, B.; Lewis, H.; Rosahl, T.; Hider, R.; Camargo, L.M.; Shearman, M.S.; Crowther, D.C.; et al. (European Journal of Neuroscience, 2009)
The mechanism by which aggregates of the beta-amyloid peptide (Abeta) mediate their toxicity is uncertain. We show here that the expression of the 42-amino-acid isoform of Abeta (Abeta(1-42)) changes the expression of genes involved in oxidative stress in a Drosophila model of Alzheimer's disease. A subsequent genetic screen confirmed the importance of oxidative stress and a molecular dissection of the steps in the cellular metabolism of reactive oxygen species revealed that the iron-binding protein ferritin and the H(2)O(2) scavenger catalase are the most potent suppressors of the toxicity of wild-type and Arctic (E22G) Abeta(1-42). Likewise, treatment with the iron-binding compound clioquinol increased the lifespan of flies expressing Arctic Abeta(1-42). The effect of iron appears to be mediated by oxidative stress as ferritin heavy chain co-expression reduced carbonyl levels in Abeta(1-42) flies by 65% and restored the survival and locomotion function to normal. This was achieved despite the presence of elevated levels of the Abeta(1-42). Taken together, our data show that oxidative stress, probably mediated by the hydroxyl radical and generated by the Fenton reaction, is essential for Abeta(1-42) toxicity in vivo and provide strong support for Alzheimer's disease therapies based on metal chelation.